The Frankfurt Complaint Questionnaire for self‐assessment of basic symptoms in the early detection of psychosis—Factor structure, reliability, and predictive validity. Issue 2 (21st December 2017) - Uttinger, Martina; Studerus, Erich; Ittig, Sarah; Heitz, Ulrike; Schultze‐Lutter, Frauke; Riecher‐Rössler, Anita
Abstract: Objectives: Patients with schizophrenia often experience subtle disturbances in several domains of information processing—so‐called basic symptoms (BS). BS are already present before onset of frank psychosis and can be assessed by interviews but also by the self‐administered Frankfurt Complaint Questionnaire (FCQ). We investigated the factor structure, reliability, and predictive validity for transition to psychosis of the FCQ, comparing previously proposed factor solutions containing 1, 2, 4, and 10 factors. Methods: Confirmatory factor analysis was used in a sample of 117 at‐risk mental state and 92 first‐episode psychosis participants of the Basel FePsy (early detection of psychosis) study. Results: Although all factor models fitted to the data, the 2‐ or 4‐factor solutions performed best among the models that used at least half of the FCQ items, suggesting the covariance between FCQ items is best explained by 2 to 4 underlying factors. No FCQ‐scale predicted transition to psychosis. Conclusion: We could confirm a 2‐ to 4‐factor structure of the FCQ in a sample of at‐risk mental state and first‐episode psychosis patients using confirmatory factor analysis. Contrary to interview‐assessed cognitive–perceptive BS, self‐assessed BS do not seem to improve prediction of psychosis. This result reinforces reports of poor correspondence between interview‐ and questionnaire‐assessed BS.